Seasonal variations of epipelic diatoms in Gölbaşi Lake with relation to physical-chemical variables - Cetin, A.K.; Sen, B.; Yildirim, V. (My University, 2002)
Epipelic diatoms were collected monthly for a year from five sampling stations in the Gölbaşi Lake to investigate the relationship between seasonal variations of epipelic diatoms and environmental factors. A total of seventy diatom taxa were determined. Cyclotella comta, C. meneghiniana, C. ocellata, Navicula cryptocephala and N. reinhardii were the most conspicuous diatoms in terms of frequency of occurrence and relative abundance in the epipelic community. Some of the epipelic diatoms were noticeable for their occurrence only at certain sampling stations. Water temperature was found to be a more important factor in steering the growth of epipelic diatoms in this study.
Keywords: Diatom; Epipelic; Freshwater; Gölbaşi Lake; Turkey